Comment on "Tectono Metamorphic Evolution of the Central Ribeira Belt, Brazil: A Case of Late Neoproterozoic Intracontinental Orogeny and Flow of Partially Molten Deep Crust During the Assembly of West by Meira et al. Issue 7 (11th July 2020) - Heilbron, Monica; de Morisson Valeriano, Claudio
Key Points: Well‐documented subduction‐related magmatic arcs and multiple collisions were not addressed in the proposed intracontinental model Partial review of the literature and issues regarding interpretation of data should be considered Abstract: The commented article contributes with new metamorphic petrology and U‐Pb geochronology data concerning the sin‐collisional stage of two terranes (Embu and Costeiro) belonging to the southern Ribeira orogen (not Central Ribeira belt, as the title suggests), in order to propose an intracontinental evolution for the Ribeira‐Araçuaí orogenic system. Several issues regarding their review of the literature and interpretation of data should be considered in face of the proposition for an intracontinental evolution of an orogenic system that has long been considered as having developed through a Wilsonian sequence of events, involving continental rifting and ocean development, subduction and building of magmatic arc, terrane accretion, and continental collision in the context of amalgamation of Gondwana. In order to contribute to a comprehensive discussion of the tectonic evolution of the Ribeira‐Araçuaí orogenic system, we bring forward the following points that have not been properly acknowledged by the authors in their proposed tectonic scheme. Without substantial new data set and without integrating all the available age, petrologic and deformational data, there seems not to be commented enough evidence for the proposal of an intracontinental evolution for the Ribeira‐Araçuaí orogenic system. In contrary, an accretionary to collisional model is preferred because it in fact integrates all the documented tectonic features: subduction of passive São Francisco paleocontinental margin, generation of magmatic arcs with typical signatures of modern ones elsewhere in the world, three accretionary‐collisional episodes, and an episode of orogenic collapse in the Cambro‐Ordovician transition, associated to slab breakoff and upwelling of asthenosphere.